PENGEMBANGAN USAHA KECIL CETHOK DI KAMPUNG TEPI SUNGAI, BRATANG TANGKIS, SURABAYA - Priskila Adiasih (SHARE: Journal of Service Learning, 2014)
Recycling polyvinylchlorida pipe (PVC) or paralon to a trowel can be a tool to emerge from the economic downturn as well as forming cekom (cethok komunitas). Service learning activities by the Business Information Systems class is expected for students to improve their ability to interact with local community, to do a SWOT analysis, to develop a simple bookkeeping, to promote the trowel through a blog that is useful for the business community to develop their business.